Analisis Faktor-Faktor Yang Mempengaruhi Non Performing Financing (Npf) Di Industri Bank Pembiayaan Rakyat (Bpr) Syariah Di Indonesia - Achmad Yasin (AKRUAL: JURNAL AKUNTANSI, 2014)
AbstractThe study was conducted to examined and analyzed factors that affect non-performing finance in Islamic Rural Bank Industry in Indonesia. The study used quantitative approach with time series data in the form of Islamic Rural Bank financial report of the first quarter of 2007 to the second quarter of 2014. There were 163 Islamic Rural Banks used as sample which was analyzed by multiple regression analysis. The result indicated that Gross Domestic Product (GDP), inflation rate (INF), ratio of the revenue sharing to total financing (MMR), and margin murabahah affected NPF, whereas FDR had no effect to NPF of Islamic Rural Bank in Indonesia.